The effect of the integration order used for the formation of fluid surface stiffness on the behavior of fluid - Calayir, Y; Dumanoglu, AA (Civil Comp Press, 1995)
[Abstract Not Available]
6th International Conference on Civil and Structural Engineering Computing/4th International Conference on the Application of Artificial Intelligence to Civil and Structural Engineering -- AUG 28-30, 1995 -- CAMBRIDGE, ENGLAND